Pemberdayaan Masyarakat Lokal Melalui Produksi Virgin Coconut Oil Di Dusun Nyama : Indonesia - Rumtutuly, Fransheine; Daniel Keipau; Nikolas Ngilamele; Rahel Louk; Angganita Perasoa; Rode Koupun; Vina Tetiwar; Jean Kelmaskosu; Ridolvina Unawekla; Windya Sairdola; Ismo Lellola; Asmirani Alam; Sigit Sugiarto; Juwaher Makatita (Fakultas Teknik Universitas Cenderawasih, 2023)
Geographically, Nyama Yang Hamlet is located on Moa Island, Southwest Maluku Regency, which has very rich natural resource potential, with the potential for coconut plantations. The right skills training can help increase productivity and create jobs. Answering these problems, the main purpose of this community service activity is to provide education and knowledge to the public about the benefits and process of making VCO. This service activity uses a descriptive method whose implementation begins with a preliminary study, mentoring and guidance, processing and production training, marketing, promotion, and evaluation using pretest and posttest to assess program effectiveness. The results of the questionnaire showed that 20 Nyama hamlet residents who participated in the training activities did not know how to process VCO. 3 people or 15% of residents do not know the benefits of VCO. However, after the activity ended, the results of the questionnaire showed that 100% of the residents of Nyama Hamlet were skilled in processing VCO and understood the various benefits of VCO both in daily life and having a high selling value.